Absence of Histones from the Chromosomal Proteins of Fungi - Leighton, T. J. (1971)
Interphase chromosomes were isolated in good yield from four species of fungi. In no case does the chromatin contain histones such as are characteristic of the chromosomes of other eukaryotic organisms.